Prevalence of Lactobacillus bulgaricus and Streptococcus thermophilus stability in commercially available yogurts in Sri lanka - Ranasinghe, JGS; Perera, WTR (Asian Journal of Medical Sciences, 2016)
Aims and Objectives: Common starter cultures found in fermented milk products are Lactobacillus bulgaricus and Streptococcus thermophilus. The viability of these bacteria is important in order to gain health benefits. It is important to investigate the stability of commercially available yogurts with respect to starter cultures and the quality. Materials and Methods: Yogurt samples were collected from highly marketed different brands designated as A, B, C, D, E, F, G and H from different areas from Sri Lanka. MRS and M17 agar were used to enumerate L. bulgaricus and S. thermophilus respectively and a pH change was measured. Results: The pH values decreased significantly and only two of these products maintained 106 cfuml-1 viable count of L. bulgaricus till the end of the shelf life. All products showed the highest number of S. thermophilus. Conclusion: The pH of the yoghurts significantly change with the storage. For optimum benefits, the yogurt products should be consumed within seventh to fourteenth day from its manufacturing date. Only two of the yoghurt products maintained 106 cfuml-1 viable count of L. bulgaricus till the end of the expiry. Asian Journal of Medical Sciences Vol.7(5) 2016 97-101